Measuring the Outcome of Perpetrator Programmes through a Contextualised and Victim-Centred Approach: The Impact Project - Berta Vall; Jaume Grané Morcillo; Alessandra Pauncz; Marianne Hester (Social Sciences, 2023)
Intimate partner violence (IPV) is a public health and widespread problem, and perpetrator programmes are in a unique position to prevent it. Research on the outcomes of perpetrator programmes has advanced in recent years, but still some challenges remain. These challenges include the absence of measures related to survivor safety and wellbeing as well as the impact on the victim. Additionally, other contextual measures, such as motivation to change or taking responsibility, are typically not included in outcome studies. The Impact Outcome Monitoring Toolkit was developed to help overcome these challenges. The participants were 444 men enrolled in a perpetrator programme and their (ex-)partners (n = 272). The results showed that all types of violence were reduced significantly in terms of both frequency and presence, as reported by both the men enrolled in the programme and their (ex-)partners. The impact of violence had been reduced for (ex-)partners, but some still suffered impacts and felt afraid. The results on the impact of violence on children and improved parenting were quite concerning. The Impact Toolkit makes it possible to measure the outcomes of perpetrator programmes in a contextualised manner and has shown promising results, supporting the inclusion of survivor-centric outcome measures.